Effectiveness of Nutrition Education in Improving Students Knowledge of Reproductive Health at SMK Wira Harapan (JURNAL PENGMAS KESTRA (JPK), 2025)
Adolescence is a crucial phase of development in the human life cycle, marked by physical and psychological changes as well as complex social dynamics. During this phase, adolescents need adequate knowledge about their physical health, including reproductive health, as a basis for developing responsible health behaviors. A lack of knowledge about reproductive health can increase the risk of unhealthy behaviors that have a negative impact on long-term health. This Community Service Activity (PKM) aims to improve students' knowledge of reproductive health through interactive approaches and nutrition education. The methods used include delivering material through interactive lectures, discussions, and evaluations using pre-tests and post-tests. The pre-test results showed that the average knowledge score was only 63.6%, while the post-test score reached 97.1%. This 33.5% increase indicates a very significant improvement in knowledge. Systematic education has proven to play an important role in improving adolescent reproductive health literacy and contributing to the formation of better health behaviors in the future. This PKM activity not only increased students' knowledge but also shaped positive attitudes about the importance of maintaining reproductive health. The PKM activity thus makes a tangible contribution to the promotion and prevention of adolescent reproductive health and has the potential to support improvements in the health of the younger generation in the future.